A novel role for melatonin: regulation of the expression of cell adhesion molecules in the rat hippocampus and cortex - Baydas, G; Nedzvetsky, VS; Nerush, PA; Kirichenko, SV; Demchenko, HM; Reiter, RJ (Elsevier Sci Ireland Ltd, 2002)
Neural cell adhesion molecules (NCAMs) are members of the immunoglobulin superfamily and are involved in synaptic rearrangements in the mature brain. There are three major NCAM forms: NCAM 180, NCAM 140 and NCAM 120. Several studies report that NCAMs play a central role in memory. In the present study we investigated the effects of melatonin on the expression of NCAMs in the hippocampus, cortex and cerebellum. The levels of NCAMs were determined by Western blotting. After administration of melatonin for 7 days, NCAM 180 expression increased both in the hippocampus and in the cortex as compared to controls. On the contrary, in rats exposed to the constant light for 7 days (which inhibits endogenous production of melatonin), NCAM 180 levels decreased in the hippocampus and became undetectable in cortex and cerebellum. NCAM 140 levels were also diminished in the hippocampus of constant light-exposed rats. There was no change in NCAM 120 expression in any brain regions. This is the first report indicating that melatonin has a modulatory effect on the expression of NCAM in brain areas concerned with cognitive function. Melatonin may be involved in structural remodeling of synaptic connections during memory and learning processes. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: melatonin; neural cell adhesion molecule; constant light; memory